Decrease in errors at solution of problems of heat conductivity by finite element method - S. V. Fedorov (Омский научный вестник)
The method of the choice of a step on time at the solution of non-stationary problems of heat conductivity is presented in the article. Comparison with the analytical decision is made. The algorithm of the choice of a step in the automatic mode is offered. Application of this technique allows to reduce significantly expenses of machine time for carrying out calculation of the nonstationary temperature field without error in accuracy. The specified technique is realized in the Temper-3D program used for performance of heat technical calculations of the protecting designs.